The Shérazade Files: Journalism, Literature, and the Subject of Immigration. - Dobie, deleine (Esprit Createur)
Leïla Sebbar's Shérazade, 17 ans, brune, frisée, les yeux verts (1982) was one of the first French novels to explore the experiences of the 'beur generation.' The titular description of a teenaged runaway reads like a fait divers in a local newspaper, and indeed, the novel engages with media depictions of immigrant communities. This article explores its relation, not only to mainstream media but also to publications that sought to counteract dominant narratives. It examines Sebbar's literary writing alongside her career as a columnist for Sans frontière , a journal 'for and by immigrants,' highlighting close thematic and stylistic links and proposing that the journal can be viewed as an epitext of the novel.